1365. a) \( 3^{x-3^{x+3}=-78} \) б) \( 5^{2 x-1}-5^{2 x-3}=4,8 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
First, let's tackle the equation \( 3^{x} - 3^{x+3} = -78 \). We can rewrite \( 3^{x+3} \) as \( 3^{x} \cdot 3^{3} = 27 \cdot 3^{x} \). Thus, the equation becomes: \[ 3^{x} - 27 \cdot 3^{x} = -78 \] This simplifies to: \[ -26 \cdot 3^{x} = -78 \] Dividing both sides by -26, we find: \[ 3^{x} = 3 \] Taking logarithms or recognizing the powers, we conclude: \[ x = 1 \] Now, for the second equation \( 5^{2x-1} - 5^{2x-3} = 4.8 \), let's make a substitution. Let \( y = 5^{2x} \). Then, we can express the equation as: \[ \frac{y}{5} - \frac{y}{125} = 4.8 \] Multiplying through by 125 to eliminate the fractions gives: \[ 25y - y = 600 \] Simplifying further, we find: \[ 24y = 600 \] From this, we get: \[ y = 25 \] Recall our substitution \( y = 5^{2x} = 25 \). This means: \[ 5^{2x} = 5^{2} \] So, \[ 2x = 2 \] and consequently: \[ x = 1 \] Thus, the solutions are: a) \( x = 1 \) b) \( x = 1 \)